Dysregulation of lncRNA GATA3-AS1 is Involved in the Pathogenesis of Pulpitis by the Regulation of miR-17-3p - Li L; Wang Y; Hu M (Journal of Inflammation Research)
Leilei Li,1,* Yumei Wang,2,* Mingyan Hu1 1Department of Stomatology, Dongying People’s Hospital, Dongying, Shandong, People’s Republic of China; 2Department of Stomatology, Dongying District People’s Hospital, Dongying, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingyan Hu, Department of Stomatology, Dongying People’s Hospital, No. 317 Nanyi Road, Dongying, Shandong, 257091, People’s Republic of China, Tel +86-0546-8901234, Email Humingyanwork@163.comPurpose: When the pulp is inflamed or injured, cell morphology, gene expression, and synaptic connections change occur in the medullary dorsal horn, causing inflammation pain and formatting the pulpitis pain. To examine the impact of lncRNA GATA3-AS1 regulation of miR-17-3p on bioactivity and inflammation of lipopolysaccharides (LPS)-stimulated human dental pulp stem cells (hDPSCs).Patients and Methods: The GATA3-AS1 expression in serum samples from patients with pulpitis, dental caries, and healthy control was examined using RT-qPCR. The GATA3-AS1 expression was verified using the GSE198359 dataset. hDPSCs were exposed to LPS to mimic in vitro pulpitis model. The viability and apoptotic rates of hDPSCs were determined by CCK-8 method and Flow cytometric analysis. The inflammatory cytokines levels were quantified using ELISA-based approach. A SOD assay kit was utilized to measure the activity of SOD. Bioinformatic analysis and dual-luciferase reporter assay were performed to explore the interaction between GATA3-AS1 and miR-17-3p, along with the potential mechanism.Results: Serum and tissue GATA3-AS1 levels were elevated in patients with pulpitis. Silencing GATA3-AS1 overturned the LPS stimulation inhibited viability and promoted apoptosis, inflammation, and oxidative stress in hDPSCs. GATA3-AS1 could target miR-17-3p, and miR-17-3p downregulation reversed silencing GATA3-AS1-mediated effects in LPS-induced hDPSCs. The GATA3-AS1-miR-17-3p axis might mediate the progression of pulpitis by many potential pathways, such as the PI3K-Akt signaling pathway and MAPK signaling pathway.Conclusion: GATA3-AS1 knockdown might have a protective effect on bioactivity, LPS-triggered inflammation, and damage in hDPSCs by regulating miR-17-3p, which might be a promising target for the treatment of pulpitis.Keywords: GATA3-AS1, pulpitis, inflammation, proliferation, miR-17-3p, oxidative stress